2011
DOI: 10.1016/j.ajhg.2011.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Translation Initiator EIF4G1 Mutations in Familial Parkinson Disease

Abstract: Genome-wide analysis of a multi-incident family with autosomal-dominant parkinsonism has implicated a locus on chromosomal region 3q26-q28. Linkage and disease segregation is explained by a missense mutation c.3614G>A (p.Arg1205His) in eukaryotic translation initiation factor 4-gamma (EIF4G1). Subsequent sequence and genotype analysis identified EIF4G1 c.1505C>T (p.Ala502Val), c.2056G>T (p.Gly686Cys), c.3490A>C (p.Ser1164Arg), c.3589C>T (p.Arg1197Trp) and c.3614G>A (p.Arg1205His) substitutions in affected subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
192
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 257 publications
(201 citation statements)
references
References 27 publications
7
192
0
2
Order By: Relevance
“…As previously reported (Chartier-Harlin et al, 2011), no significant association with PD was found. Our cases with p.G686C mutations had idiopathic PD, good responses to L-DOPA and no dementia, consistent with the late-onset idiopathic Lewy body parkinsonism previously reported in EIF4G1 patient carriers.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…As previously reported (Chartier-Harlin et al, 2011), no significant association with PD was found. Our cases with p.G686C mutations had idiopathic PD, good responses to L-DOPA and no dementia, consistent with the late-onset idiopathic Lewy body parkinsonism previously reported in EIF4G1 patient carriers.…”
Section: Discussionsupporting
confidence: 62%
“…Linkage and candidate gene analysis identified the p.R1205H mutation in EIF4G1, encoding a component of the eIF4F translation initiation complex that regulates cell survival in response to stressors, in a large French family with AD late-onset PD and seven smaller families of various origins, probably resulting from an ancestral founder (Chartier-Harlin et al, 2011). Screening additional patients with parkinsonism and Lewy body disease identified four less frequent putatively disease-causing mutations, p.A502V, p.G686C, p.S1164R and p.R1197W, absent from ~4,000 controls, but their involvement in disease pathogenesis remains inconclusive, in absence of segregation analyses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All novel variants were examined for disease segregation in affected and unaffected family members by additional sequencing. Evidence for segregation with disease was assessed using parametric linkage analysis, as previously described (2). All potentially pathogenic mutations were genotyped in case -control series using TaqMan probes; and mutations carriers confirmed by direct sequencing.…”
Section: Sequencing and Genotyping Analysismentioning
confidence: 99%